Investigating the role of debt advice on borrowers' well-being: An encouragement study on a new sample of over-indebted people in Britain - Laura Fumagalli; Peter Lynn; Jair Mu\~noz-Bugarin (University of Essex, Institute for Social and Economic Research (ISER), 2021)
Little is known about the effect of seeking debt advice on borrowers' well-being. To estimate this effect, we designed a randomised encouragement intervention for a new sample of over-indebted people in Britain who had not sought debt advice in the previous six months. Being encouraged to seek debt advice increases the likelihood of seeking informal debt advice (e.g., from friends), but not the likelihood of seeking formal debt advice (e.g., from governmental agencies). When asked about their well-being using standardised questions, people who received the encouragement report increased well-being, especially when asked more than a year after the encouragement. The increased well-being does not seem to be a result of improved debt-management skills. In fact, spending and financial difficulties increase as a result of the encouragement, and attitudes to debt deteriorate. We also estimate the effect of seeking informal debt advice using the receipt of the encouragement as an instrumental variable. While imprecisely estimated, these results are in line with the results on the effects of receiving the encouragement.
Keywords: 330; Psychology; Information Networks; Survey Methodology; Debt: Indebtedness; Well Being; Health; Surveys; Finance